Advanced synthesis and application of Bis[3-(triethoxysilyl)propyl]tetrasulfide hydrolysate for efficient chemical modification of silica - Kim, Dae Jin; Jung, Dong Eui; Yoo, Bok Ryul; Kim, Young-Min (SAGE Publications, 2026)
The hydrolysis of organoalkoxysilanes (OAS) is a critical step in forming covalent interfacial bonds in organic/inorganic hybrid systems. However, many OAS suffer from limited aqueous compatibility and poor silanol formation, hindering efficient surface modification. In this study, bis[3-(triethoxysilyl)propyl]tetrasulfide (TESPT), a hydrophobic OAS used in silica/rubber composites, was hydrolyzed under acidic aqueous conditions with ethanol to produce silanol-rich species. 1H NMR confirmed up to 97% silanol conversion under optimized pH, temperature, and ethanol ratios. The hydrolysates enabled covalent grafting onto silica, as confirmed by solvent washing and thermogravimetric analysis, which revealed up to 2.4 wt.% bound organic content. Enhanced surface hydrophobicity was demonstrated by contact angle (113°) and water flotation tests. When incorporated into SSBR (solution styrene–butadiene rubber) composites, the modified silica exhibited improved dispersion, yielding 25.5% bound rubber and mechanical enhancements (20.5 MPa tensile strength, 578% elongation). Vulcanization also benefited, with extended scorch time (8.9 min) and shortened cure time (23.1 min), attributed to improved thermal conductivity and filler distribution. Compared to conventional TESPT mixing, similar or better performance was achieved with reduced TESPT usage. These results highlight the importance of controlled TESPT hydrolysis for cost-effective silica surface engineering in advanced rubber composites.